2010
DOI: 10.1186/1471-2180-10-77
|View full text |Cite
|
Sign up to set email alerts
|

The PTS transporters of Lactobacillus gasseri ATCC 33323

Abstract: BackgroundLactobacilli can utilize a variety of carbohydrates which reflects the nutrient availability in their respective environments. A common lactobacilli in the human gastrointestinal tract, Lactobacillus gasseri, was selected for further study. The currently available annotation of the L. gasseri ATCC 33323 genome describes numerous putative genes involved in carbohydrate utilization, yet the specific functions of many of these genes remain unknown.ResultsAn enzyme I (EI) knockout strain revealed that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 43 publications
5
53
0
Order By: Relevance
“…First, an API 50 CH assay revealed that NCK334 could utilize lactose, while the EI knockout strain could not. Second, growth curves using sMRS supplemented with 1 % lactose confirmed the API 50 CH results (Francl et al, 2010). From these results, we concluded that PTS(s) are required for the utilization of lactose by NCK334.…”
Section: Bioinformatic Analysissupporting
confidence: 66%
See 4 more Smart Citations
“…First, an API 50 CH assay revealed that NCK334 could utilize lactose, while the EI knockout strain could not. Second, growth curves using sMRS supplemented with 1 % lactose confirmed the API 50 CH results (Francl et al, 2010). From these results, we concluded that PTS(s) are required for the utilization of lactose by NCK334.…”
Section: Bioinformatic Analysissupporting
confidence: 66%
“…On: Wed, 27 Mar 2019 22:11:11 of the PTS and potential b-galactosidase genes, as previously described (Francl et al, 2010). Relative fold change values were compared with either glucose or fructose.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations